1998
DOI: 10.1073/pnas.95.15.8939
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of the angular gyrus in normal reading and dyslexia

Abstract: The classic neurologic model for reading, based on studies of patients with acquired alexia, hypothesizes functional linkages between the angular gyrus in the left hemisphere and visual association areas in the occipital and temporal lobes. The angular gyrus also is thought to have functional links with posterior language areas (e.g., Wernicke's area), because it is presumed to be involved in mapping visually presented inputs onto linguistic representations. Using positron emission tomography , we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
336
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(376 citation statements)
references
References 36 publications
29
336
1
7
Order By: Relevance
“…Separate pathways in left and right hemispheres are integrated in the left lateralized Visual Word Form Area (VWFA), which mediates between visually specific input, and more abstract linguistic areas responsible for lexical, semantic and phonological processes. Although the precise projections from VWFA to systems involved in lexical, semantic and phonological processes are currently less clearly defined, functional areas probably include the left angular gyrus [52], left inferior frontal cortex [53], and temporal regions anterior to the VWFA [54]. Finally, ventral visual regions receive top-down attentional influences associated with left and right parietal regions that are likely to affect all processing levels, and whose impairment might therefore lead to various forms of neglect dyslexia.…”
Section: Box 2 Model Of Functional Anatomy For Invariant Word Percepmentioning
confidence: 99%
“…Separate pathways in left and right hemispheres are integrated in the left lateralized Visual Word Form Area (VWFA), which mediates between visually specific input, and more abstract linguistic areas responsible for lexical, semantic and phonological processes. Although the precise projections from VWFA to systems involved in lexical, semantic and phonological processes are currently less clearly defined, functional areas probably include the left angular gyrus [52], left inferior frontal cortex [53], and temporal regions anterior to the VWFA [54]. Finally, ventral visual regions receive top-down attentional influences associated with left and right parietal regions that are likely to affect all processing levels, and whose impairment might therefore lead to various forms of neglect dyslexia.…”
Section: Box 2 Model Of Functional Anatomy For Invariant Word Percepmentioning
confidence: 99%
“…This deficit has been associated with a dysfunction of the left ventral occipitotemporal cortex in adolescents and adults (e.g., (Brunswick et al, 1999;Helenius et al, 1999;Horwitz et al, 1998; Kronbichler et al, 2006; McCrory et al, 2005; Paulesu et al, 2001;Rumsey et al, 1997a;Rumsey et al, 1997b;Salmelin et al, 1996;Shaywitz et al, 2003; In our previous fMRI study, we specifically investigated print processing in the VWF-System in children with and without dyslexia while they indicated if visual stimuli (real words, pseudohomophones, pseudowords and false-fonts) sounded like a real word (Van der Mark et al, 2009). We found that a posterior-anterior gradient of print specificity (higher anterior activity to letter strings but higher posterior activity to false-fonts) as well as a constant sensitivity to orthographic familiarity (higher activity for unfamiliar than familiar word-forms) along the VWF-System could only be detected in controls.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…showed that functional connectivity of the left occipitotemporal gyrus with the left angular gyrus was weaker (Horwitz et al, 1998;Pugh et al, 2000) and connections between a left occipitotemporal seed region and the left inferior frontal gyrus were absent during reading (Shaywitz et al, 2003;Stanberry et al, 2006). In addition, our findings extend those of a recent fMRI connectivity study examining children with dyslexia during phoneme mapping, which did not find deviant connectivity for an occipital seed region, and focused instead on a finding of increased left inferior frontal gyrus connectivity to other frontal regions (Richards and Berninger, 2008).…”
Section: Disruption Of Roi-specific Functional Connectivity In Childrmentioning
confidence: 99%
See 1 more Smart Citation
“…Pugh et al (2000) provided evidence that dyslexia can be conceived as a disorder of relating print to sound and vice versa, which corresponds to a disruption of the projections between the IPG, and occipital as well as temporal cortical areas (Booth et al, 2004;Horwitz et al, 1998; but see Kronbichler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%